Tahlil al-Idarah li Tahsin Kafa’ah Muallimiy al-Lughah al-Arabiyyah min Khilal Muntada Istisyarah Muallimiy al-Lughah al-Arabiyyah fi Indonesia / Management Analysis For Improving Arabic Language Teachers' Competency Through The Arabic Language Subject Teachers' Deliberation Forum In Indonesia - Siti Safira Al-latifatuzzahra; Fitri Amelia; Shofil Fikri (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2024)
The research aims to provide an overview of the Arabic Language Subject Teachers' Deliberation Forum (FMGMP) in enhancing the competence of Arabic language teachers in Indonesia and describe its programs. The researcher sought to offer a deeper and more precise description of the forum and its core programs in developing and improving the quality of Arabic language teachers in Indonesia. This study is a library research employing a descriptive-analytical method. The data collection method involved reading documents from scientific research related to the topic, as well as from websites. After gathering the data, the researcher analyzed the information using the theory of Miles and Huberman, which includes data collection, data reduction by focusing on the forum's core programs, and then presenting and summarizing the findings. The study indicates that FMGMP for Arabic language teachers across Indonesia is an organization aimed at improving the quality of Arabic language education in Indonesia at all levels, from primary to secondary and higher education. Its programs include the Teachers' Conference, National Meeting, National Symposium, Training and Workshops, Exhibitions, National Celebrations, and the National Arabic Language Olympiad. Through these programs, FMGMP seeks to provide a range of activities specifically designed to develop teachers' educational competencies, enhance professionalism, and enrich their personal and social aspects.المستخلص: البحث يهدف إلى تقديم لمحة عن منتدى استشارة معلمي مادة اللغة العربية في تعزيز كفاءة معلمي اللغة العربية في إندونيسيا وتوصيف برامجها. سعت الباحثة إلى وصف المنتدى وبرامجه الأساسية في تطوير وتحسين جودة معلمي اللغة العربية بإندونيسيا بشكل أعمق وأدق. وأما نوع هذه الدراسة فهي دراسة مكتبية بمنهج وصفي تحليلي، فطريق جمع البيانات هي قراءة المستندات الموجودة في الأبحاث العلمية المتعلقة بالموضوع، وكذا من المواقع الإلكترونية. بعد أن تم الجمع، حللت الباحثة المعلومات معتمدة على نظرية ميلس وهوبرمان، وهي جمع البيانات، ثم تقليل البيانات بالتركيز على البرامج الأساسية لهذا المنتدى، ثم عرضها وتلخيصها. يشير البحث إلى أن منتدى استشارة معلمي مادة اللغة العربية لمعلمي اللغة العربية في جميع أنحاء إندونيسيا هي منظمة تهدف إلى تحسين جودة تعليم اللغة العربية في إندونيسيا على جميع مستويات التعليم، من الابتدائي إلى الثانوي والعالي. هناك البرامج، وهي مؤتمر المعلمين، والاجتماع الوطني، والندوة الوطنية، والتدريب وورش العمل، والعروض، الاحتفالات الوطنية، والأولمبياد الوطني للغة العربية. من خلال هذه البرامج، يهدف منتدى استشارة معلمي مادة اللغة العربية إلى تقديم مجموعة من الأنشطة المصممة خصيصًا لتطوير كفاءة تعليمية المعلمين، وزيادة الاحترافية، وتغني الجوانب الشخصية والاجتماعية.